A novel missense mutation pattern of the GCH1 gene in dopa-responsive dystonia Novo padrão de mutação missense no gene GCH1 na distonia dopa-responsiva - Rosana H. Scola; Carla Carducci; Vanise G. Amaral; Paulo J. Lorenzoni; Helio A.G. Teive; Teresa Giovanniello; Lineu C. Werneck (Arquivos de Neuro-Psiquiatria)
Dopa-responsive dystonia (DRD) is an inherited metabolic disorder now classified as DYT5 with two different biochemical defects: autosomal dominant GTP cyclohydrolase 1 (GCH1) deficiency or autosomal recessive tyrosine hydroxylase deficiency. We report the case of a 10-years-old girl with progressive generalized dystonia and gait disorder who presented dramatic response to levodopa. The phenylalanine to tyrosine ratio was significantly higher after phenylalanine loading test. This condition had two different heterozygous mutations in the GCH1 gene: the previously reported P23L mutation and a new Q182E mutation. The characteristics of the DRD and the molecular genetic findings are discussed. Distonia dopa-responsiva (DRD), classificada como DYT5, é um erro inato do metabolismo que pode ser causado por dois diferentes tipos de defeito bioquímico: deficiência de GTP ciclo-hidrolase 1 (GCH1) (autossômica dominante) ou de tirosina hidroxilase (autossômica recessiva). Descrevemos o caso de menina de 10 anos com distonia generalizada progressiva e alteração da marcha com importante melhora após uso de levodopa. A relação fenilalanina/tirosina estava aumentada após teste de sobrecarga com fenilalanina. O estudo molecular mostrou que o paciente apresenta uma combinação hererozigótica de mutação no gene GCH1: a já conhecida mutação P23L e uma nova mutação Q182E. Discutem-se as características da DRD e as alterações genéticas possíveis.